Preliminary normative data on the BORB for children aged 3–8. Issue 2 (3rd April 2019) - Brunsdon, Ruth; Joy, Pamela; Patten, Erin; Burton, Karen
ABSTRACT: The Birmingham Object Recognition Battery (BORB) is a theoretically based test battery that is used in adult cognitive neuropsychology in research and for clinical assessment. It allows a detailed analysis of underlying impairments in individuals with brain injury who have visual object recognition difficulties. The BORB's usefulness in pediatrics is supported by numerous research studies. However, there is no published normative data for children, making clinical use of the test difficult. The aim of this brief report is to publish some preliminary normative data in 70 children aged between 3 and 8 years to assist both researchers and clinicians with interpretation of test scores. Results indicate that children's performance on individual BORB subtests varies according to task demands and age. For some subtests there is improvement in performance with increasing age. However, very young children (age 3-4 years) perform at adult levels on some subtests, or alternatively on other subtests they perform at the level of chance. The current paper supports the need for pediatric data for the BORB due to large normal individual variation in performance and varying age-related performance on individual BORB subtests.